What's New about David Bentley Hart's Translation of the New Testament: Assessing Its Translation Effectiveness and Affectiveness. Issue 2 (August 2022) - Berneking, Steve
This review of David Bentley Hart's New Testament makes use of a methodological lens from the field of translation studies, that is, the translation brief. The translation brief is an agreement between the client and the translator that sets forth the essential rubrics of the project and how it will best serve the client. My review of Hart's New Testament proceeds in a similar way, identifying the translator, the purpose of the translation, the type of translation, and the audience. In addition, I offer an assessment of the effectiveness and affectiveness of his work.